SISTEM INFORMASI MONITORING PERKEMBANGAN ANAK BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Dwi Yulianto; Folanida; Rifai, Achmad (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
An effective information system in monitoring the development of children with special needs and managing information in this modern era. This research aims to develop an information system that uses the Rapid Application Development (RAD) method to monitor and manage children's development at 11 Jakarta state special schools. The RAD method is used to speed up system development, enabling the use of rapid iteration in software development for subsequent implementation at 11 Jakarta state special schools. This research involves the steps of gathering requirements from stakeholders, iterative system design, implementation, and testing to ensure the functionality and effectiveness of the system being built. The resulting system allows monitoring of the development process containing the development of children's values, health and abilities, enabling administrators and teachers to analyze development data more efficiently and in more detail. The use of the RAD Method in developing this system provides satisfactory results with the ability to adapt to the needs of rapid changes in the 11 Jakarta state special school environment. This research shows that the application of the RAD Method in developing a child development monitoring information system has the potential to increase efficiency. The implications of the results of this research provide a basis for 11 Jakarta state special schools in adopting a software development approach that is adaptive and responsive to dynamic changing needs.